DETERMINAN KINERJA KEUANGAN PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BEI - Siti Aisya; Junita, Afrah; Mayang Murni (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
This study aims to determine the effect of company size, activity ratio, and corporate social responsibility on firm value in telecommunications companies listed on the Indonesia Stock Exchange. The subjects of this study were telecommunications companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling. Data collection was based on historical company data, namely audited financial data from telecommunications companies listed on the IDX for the period 2019-2023. The data analysis method used in this study was multiple linear regression analysis using SPSS (Statistical Package for the Social Science) software. The results of this study indicate that company size and activity ratio have a positive and significant effect on firm value in telecommunications companies. However, corporate social responsibility is not significant. Simultaneously, company size, activity ratio, and corporate social responsibility have a significant effect on firm value in telecommunications companies. A limitation of the current research is that it focused solely on telecommunications companies listed on the Indonesia Stock Exchange (IDX), so the results may not be generalizable to other industrial sectors. It is recommended that the research be expanded to include companies in other industrial sectors or telecommunications companies in other countries to compare the results and gain broader insights.